By What Criteria Do We Evaluate Accounting? Some Thoughts on Economic Welfare and the Archival Literature - BALL, RAY (Journal of Accounting Research, 2024)
ABSTRACT The economic role of an accounting regime is to increase welfare through its effects—in conjunction with complementary institutions—on firm and household behavior. I review three major streams of the archival literature (real effects; price effects, including value relevance; and costly contracting), in terms of what they can and cannot reveal as proxies for welfare effects. One conclusion is that the partial correlations and average effects that predominate in this literature have provided valuable insights into the role of accounting in the economy, but provide limited and misleading proxies for welfare effects. A major concern is that teachers, students, and researchers—indeed, regulators and standard setters—raised on this literature could lose sight of, and underestimate, the fundamental contribution of accounting to aggregate welfare.